Efeitos do laser de baixa intensidade e do exercício físico aeróbio sobre a regeneração do músculo tibial anterior de ratos - Adabbo, Mayna (Universidade Federal de São Carlos, 2012)
The objective of this study was to analyze the effects of Low level laser therapy (LLLT) associated with aerobic physical exercise on the muscle regeneration process during 2 periods of rest after of the muscle injury in rats. Forty rats were divided into 2 groups (A and B), and 4 subgroups each: GC (Control Group) - cryolesioned untreated; GE (Exercise Group) - cryolesioned treated with aerobic physical exercise; GL (Laser Group) - cryolesioned treated with laser; GEL (Exercise and Laser Group) - cryolesioned treated with laser and aerobic physical exercise. The tibialis anterior (TA) of the middle belly was injured by a cooling iron bar (cryoinjury). The animals in Group A remained at rest for 3 days, while Group B remained at rest for 7 days. The laser parameters were: 780 nm, 15 mW, during 10 s, 0.152 J e 3.8 J/cm². Physical exercises with or without laser were performed during 5 days, each session lasting 12 min at a treadmill velocity of 17 m/min. The AT muscles were removed for histological and morphometric analysis. The damage area was significantly smaller for the GEL, when remained at rest for 3 and 7 days respectively, (4.4±0.42 % and 3.5±0.14 %, p < 0.05) compared to GL (18.6±0.64 % and 7.5±0.13 %), GE (21±0.26 % and 8.7±0.32 %) and GC (23.9±0.37 % and 21.4±0.38 %). In addition, the number of blood vessels were significantly higher for the GEL, when remained at rest for 3 and 7 days respectively, (71.2±13.51 % and 104.5±11,78, p < 0.05) compared to the GL (60.6±11.25 and 93.5±16.87), GE (51.6±7.3 and 93.8±15.1) and GC (34.4±2.54 and 65.7±14.1). Therefore, the laser applied before the physical exercise on the treadmill stimulated an angiogenesis and accelerated the process of muscle regeneration.
Keywords: Biotecnologia; Lesão muscular; Regeneração do músculo esquelético; Laserterapia; Atividade física; Laser de baixa intensidade; Exercício físico aeróbico; Reparo muscular; Low level laser therapy; Aerobic exercise; Muscle repair; OUTROS